(untitled) (Journal of Comparative & International Higher Education, 2023)
During the COVID-19 pandemic, digitalisation in the international higher education sector was underlined by migration to online delivery across different educational contexts. However, research into the execution of digitalisation together with its impacts on the teaching and learning of international students in higher education is scattered and fragmented. This study aims to systematically review articles related to these topics based on a four-step refined process: initial search, filtering, screening, and in-depth review. Thirty-five identified articles were used to examine (1) the main forms of digitalisation of teaching and learning for international students, (2) the digitalization-related experience of international students in learning, (3) the opportunities of digitalisation of teaching and learning for international students and (4) the challenges of digitalisation of the teaching and learning for international students. Based on the findings, we discuss the implications of capitalizing on digital technologies and refining pedagogies in online and blended modes of delivery.